Răspuns :
c=2^(n+2) x3^(n+1) +2^(n+1) x3^(n+2) +2^(n+2) x3^(n+2)
Factor comun 2^(n+1) x3^(n+1):
c=2^(n+1) x3^(n+1) x(2x1+1x3+2x3)=11x 2^(n+1) x3^(n+1)
c=11x 2^(n+1) x3^(n+1)
Prin urmare c este multiplu de 6 si se divide cu el.
Factor comun 2^(n+1) x3^(n+1):
c=2^(n+1) x3^(n+1) x(2x1+1x3+2x3)=11x 2^(n+1) x3^(n+1)
c=11x 2^(n+1) x3^(n+1)
Prin urmare c este multiplu de 6 si se divide cu el.
2ⁿ⁺² × 3ⁿ⁺¹+ 2ⁿ⁺¹ × 3ⁿ⁺²+ 6ⁿ⁺²= 2ⁿ×2²×3ⁿ×3 + 2ⁿ×2×3ⁿ×3² + 6ⁿ×6²=
=6ⁿ×2²×3 + 6ⁿ×2×3² + 6ⁿ×6²= 6ⁿ×(2²×3 + 2×3²+6²)= 6ⁿ×(12+18+36)=
=6ⁿ× 66 si 11| 66×6ⁿ
=6ⁿ×2²×3 + 6ⁿ×2×3² + 6ⁿ×6²= 6ⁿ×(2²×3 + 2×3²+6²)= 6ⁿ×(12+18+36)=
=6ⁿ× 66 si 11| 66×6ⁿ